Accountability and the law : rights, authority and transparency of public power - Mikuli, Piotr, 1977-; Kuca, Grzegorz (Comparative constitutional change., 2022)
"This book combines conceptual insights into what shapes contemporary accountability mechanisms with a selection of case studies. The volume analyses and discusses issues related to the accountability and transparency of public power. The authors deal with various problems connected to controlling public institutions and incumbents' responsibility in state bodies. The work is divided into three parts: Part I: Law examines the institutional and objective approach. Part II: Fairness and Rights discusses the subject approach, referring to a recipient of rights. Part III: Authority looks at the functional approach, referring to the executors of law. Providing insights into increasing understanding of various concepts, principles and institutions characteristic of the modern state, the book makes a valuable contribution to the area of comparative constitutional change. It will be a valuable resource for academics, researchers and policy makers working in the areas of Constitutional Law and Politics"--